The fire your boss, do what you love and work better to live more - Chris, Guillebeau (London Macmillan, 2012)
You no longer need to work nine-to-five in a big company to pay the mortgage, send your kids to school and afford that yearly holiday. You can quit the rat race and start up on your own ? and you don't need an MBA or a huge investment to do it.
Keywords: New business enterprises -- Case studies; Alternative lifestyles -- Case studies